2013
DOI: 10.3109/08941939.2013.826308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ankaferd on Anastomotic Healing of Colon

Abstract: ABS may support anastomotic healing in septic conditions. Topical ABS application controlling the mucosal bleeding at the cut ends of the colon may also improve the anastomotic wound healing by means of increasing mechanical strength and positively affecting angiogenesis. Further studies shall focus on the clinical importance of those findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…Our study showed that ABS decreases collagen bundle organization, which is one of the indicators of the healing process. However, Cancan et al [7] showed that topical ABS improves collagen production, and may support anastomotic healing in septic conditions in rats. These opposite results may be secondary to the different aseptic surgical and aseptic healing conditions that exist between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study showed that ABS decreases collagen bundle organization, which is one of the indicators of the healing process. However, Cancan et al [7] showed that topical ABS improves collagen production, and may support anastomotic healing in septic conditions in rats. These opposite results may be secondary to the different aseptic surgical and aseptic healing conditions that exist between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study which was performed to evaluate radiologic results and serum changes of oxidative stress markers during fracture healing process with and without ABS application to bone fracture, it was shown that ABS was ineffective on fracture healing in early healing period except for bleeding control. [33] Cancan et al [7] studied the effects of ABS on colonic anastomosis. They showed that ABS may support anastomotic healing in septic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations